1985
DOI: 10.1017/s0022172400061477
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and automated detection of salmonella by electrical measurements

Abstract: SUMMARYA rapid method for determining the presence of salmonella in food is described. It consists of pre-enrichment in buffered peptone water modified by the addition of dulcitol and trimethylamine oxide, followed by selective enrichment in a selenite-cystine broth with similar modifications. Changes in the conductance of the selective enrichment broth are monitored continuously using a suitable impediometric instrument. Most of the Salmonella spp. tested gave a fast (-100 #1S/h) and large (> 600 itS) change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…Numerous papers have been published on the subject of media engineering for Salmonella detection with emphasis on the optimization of the electrical signal and the support of selective growth of Salmonella. The initial impedance detection medium for Salmonella was selenite-cystine/trimethylamine oxide/dulcitol (Easter and Gibson, 1985). Due to negative results for some Salmonella strains, dulcitol in the medium was replaced by mannitol (Gibson, 1987;Ogden and Cann, 1987).…”
Section: Classic Impedance Microbiologymentioning
confidence: 99%
“…Numerous papers have been published on the subject of media engineering for Salmonella detection with emphasis on the optimization of the electrical signal and the support of selective growth of Salmonella. The initial impedance detection medium for Salmonella was selenite-cystine/trimethylamine oxide/dulcitol (Easter and Gibson, 1985). Due to negative results for some Salmonella strains, dulcitol in the medium was replaced by mannitol (Gibson, 1987;Ogden and Cann, 1987).…”
Section: Classic Impedance Microbiologymentioning
confidence: 99%
“…It has been reported that 927 outbreaks of foodborne disease (36,479 cases) took place in Japan in 1989.1} Of these, 146 outbreaks (6,750 cases) were caused by Salmonella.Ĉ onventional Salmonella detection from foods requires a minimumof 4 days after sample receipt to obtain presumptive results. Rapid detection of Salmonella in foods is important for quality assurance in the food industry.…”
Section: Foodborne Illnessmentioning
confidence: 99%
“…These include electrical methods (Easter and Gibson 1985), immunoassays (e.g. Jones et al 1995), immunomagnetic separation (e.g.…”
Section: Introductionmentioning
confidence: 99%